Multiple scaring cutaneous erosions and hoarseness in a 7- month- old infant - Farsi, Yeganeh; Abdollahimajd, Fahimeh (Student Research in Translational Medicine, 2022)
A seven-month-old female infant was referred to the dermatology clinic due to several erosive cutaneous lesions. The lesions were crusted and super-infected (impetiginized), widespread on her face, trunk and, extremities. Multiple atrophic and ice-pick scars were also remarkable, especially on her face, which was attributable to previous lesions. The lesions have been appeared since one- month of age, and have been resolved on their own with atrophic scars. Hoarseness was another notable finding in her physical examination and the physical examination was otherwise normal. The hoarseness had existed since her birth. Lipoid proteinosis or Urbach- Weithe syndrome is a rare autosomal recessive disorder due to mutation in extracellular matrix protein 1 (ECM 1) characterized by the deposition of hyaline in cutaneous tissue and mucus membrane of aerodigestive tract (2). Mucocutaneous lesions including palpebral and lingual yellowish nodules, laryngeal complications such as hoarseness and obstruction, and neuro-cognitive disorders including learning difficulties, aggression, loss of fear, memory impairment, and seizures are expected in lipoid proteinosis (3-7).